The Role Management In Improving Employees Performance )Field Study At Tishreen University) - تركمان, حنان (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study aime to clarify the concept of management, its importance, dimensions and requirements for its application in the organization under study, and to clarify the role of applying performance management in achieving success for the organization. The researcher followed the descriptive and analytical approach in her study, and a set of methods, including relying on secondary and primary data through a questionnaire that was designed, and it was distributed to (119) respondents, from which (117) were retrieved, and (110) questionnaires were suitable for analysis, and the research community was made up of a cadre Workers at Tishreen University in Lattakia Governorate (university president, department heads, divisional heads, and employees), and then relied on the SPSS program as a tool for analyzing the available data. The study found a set of results, including: The employee is not involved in planning and goal-making, performance is not linked to opportunities for promotion, and the levels of behavioral competence required in the employee are not determined.